A Phonological Analysis of English Loanwords in Spanish Language using Distinctive Features - Ana Puspitasari; Agus Subiyanto (Indonesian Journal of EFL and Linguistics, 2020)
Loanwords occur as the result of language contacts within the community. In Spanish language, there are borrowing words existing as the effect of the contact with English language. This research aimed at finding out the phonological process in Spanish vocabulary which were absorbed or borrowed from English language. Distinctive features were used as the approach. The research conducted was qualitative descriptive. It used 30 Spanish vocabulary borrowed from English language as the object. At the end of this research, it was found out that the phonological process which happened, involved substitution processes; not only in the consonant phonemes but also in vowel phonemes.